Development of literacy-based learning for Pancasila and citizenship education in senior high school - Nuryati Nuryati; Ahmad Nasir Ari Bowo; Paiman Paiman (Universitas Ahmad Dahlan, 2021)
Pancasila is the five principles which becomes the Indonesian ideology. The literacy culture of students, especially in Pancasila and citizenship education learning, is still low. The results of a preliminary observation we did at several high schools in Bantul Regency, Yogyakarta, showed that the problem of Pancasila and citizenship education learning was the students' low literacy skills. Solutions are needed to overcome these problems. An alternative solution about literacy based on Pancasila and citizenship education learning model is needed. The citizenship education learning process based on literacy can improve the literacy skills of students. The purpose of this study is to produce a literacy-based Pancasila and citizenship education learning model in senior high school. This type of research is qualitative. The location of this research is senior high schools in Bantul, Yogyakarta. The results showed that the literacy based on Pancasila and citizenship education learning model in senior high schools were: first, school support about literacy culture. Literacy culture facilities include education and school policies and school facilities. Second, the development of literacy based on Pancasila and citizenship education learning include: (1) preliminary stages include: orientation, apperception, motivation, and giving ignorance. Literacy developed is cultural literacy. (2) The core stages include stimulation, problem statements, data collection, verification, and concluding. The literacy developed is cultural literacy, literacy, digital literacy, and scientific literacy. (3) The concluding stage includes summarizing conclusions, reinforcement, feedback, and closing greetings. Literacy activities developed are cultural literacy and reading-writing literacy.